Evaluation of mulch practices on growth and yield of four Lisianthus (Eustoma grandiflorum) germplasm: Mulch practices on Lisianthus germplasms - Sultana, Most Naznin; Khan, Farjana Nasrin; Husna, Asmaa Ul; Maliha, Maisha; Uddin, AFM Jamal (SAARC Journal of Agriculture, 2022)
An experiment was conducted in the horticultural farm at Sher-e-Bangla Agricultural University, Dhaka to evaluate the Mulch practices on Growth and yield of four Lisianthus germplasm. The experiment consisted of four treatments (Mo: Control, Ms: Straw mulch, Mc: Cocodust mulch, Mbp: Black polythene mulch) and four Lisianthus germplasms (V1: Arena Type Pure White,V2: Double Pure White, V3: Arena Type Light Pink, V4:Super Magic Type Blue), laid out in a Randomized Complete Block Design (RCBD) with three replications. The results showed significant variations among the four varieties and different mulches. The tallest plant (71.6 cm), thickest stem (5.7 mm) and the largest flower size (70.6 mm) were found in V4 (Super magic type Blue) than others. Plants grown in Black polythene mulch (Mbp) recorded the tallest plant (65.1 cm), highest stem dia. (5.7 mm), maximum stem number (6.4), maximum number of flowers/plant (44.7) and the largest flower size (64.9 mm) than control. Based on the above parameters, the mulches are put in order as follows Mbp ≥ Mc ≥ Ms ≥ Mo. These findings may provide useful data for the improvement of sustainable flower production of Lisianthus. SAARC J. Agric., 20(2): 157-167 (2022)